Dedication Beyond Years: An Investigation of Aging Military Reservist Volunteers in Training - Rachel L Saladaga (Randwick International of Education and Linguistics Science Journal, 2023)
This study explores the impact of aging on the physical and cognitive capabilities, as well as the motivational factors, of military reservist volunteers in Agusan del Norte, Philippines. The objective is to assess how these factors affect the performance and motivation of aging reservists. Employing a descriptive correlational research design, the study examines the relationships among variables influencing reservists' effectiveness. The findings indicate a moderate decline in aging reservists' physical attributes, including strength, agility, and flexibility, and a similar trend in cognitive functions like memory and decision-making. However, these reservists effectively adapt their practices to mitigate aging impacts. Motivation is influenced significantly by both intrinsic factors, such as career advancement, and extrinsic factors, like the sense of comradeship, with the latter exerting a slightly greater influence. The study recommends that the Department of National Defense and the Armed Forces of the Philippines adopt adaptive training programs and cognitive enhancement workshops for aging reservists. Additionally, the Technical Education and Skills Development Authority and other educational bodies should develop veteran-focused programs and educational incentives to support career advancement and lifelong learning. The Department of Social Welfare and Development can further support aging reservists through community development projects, leveraging their experience and fostering a sense of purpose and community engagement.